# Can you explain how to solve 4(y+1)=2(y-2)

The numbers in brackets are powers

To answer this question you must first multiply out the powers in brackets on each side of the brackets and then collect the unknowns on one side just as you would do when solving algebraic equations.
javaid.aslam
19 June 2011
Can you guess what to do next???
javaid.aslam
19 June 2011
So it would become 4(y) x 4(1) = 2(y) / 2(2)...this is formed by using the rules of indices
javaid.aslam
19 June 2011
I think there's a typo in the above answer. If we have the equation this multiplies out to . Moving the unknowns to one side gives us: . This simplifies to . So we get . We can check this result by substituting the answer into the original question like so: showing that , and therefore our answer is correct.
theo.cushion
20 June 2011
4 ( y + 1 ) = 2 ( y - 2) remove the brakets first rule. 4y + 4 = 2y - 4 next equal terms on to one side rule, don`t forget value signs change, also a rule 4y - 2y = - 4 - 4 There fore 2y = - 8 y = - 8/2 So... y = -4 Always work on brakets , multiplication and division signs before + and - signes. Now 2y = -8 Then y = -8/2 There fore y = - 4
Indra
01 October 2020